Disorders of intellectual development in children: approaches to diagnosis - Horishna, Nadiia; Maichuk, Oksana (Social work and education, 2022)
Children with intellectual disabilities are one of the most difficult to include in the educational process of general secondary education institutions due to their difficulties in communication, behavior, sensorimotor functioning, orientation in the environment, social adaptation, and socialization. The use of modern diagnostic tools makes it possible not only to identify intellectual development disorders, determine the degree of their complexity, but also to obtain reliable information for planning educational, psychological, pedagogical and correctional development services. In order to determine modern approaches to the diagnosis of intellectual development disorders in children, theoretical methods of analysis, synthesis, comparison and generalization of information obtained from scientific sources, regulatory documents, analytical reports, etc. were used. The results of the analysis show that disorders of intellectual development are defined as inherited or acquired brain lesions that manifest themselves during development period, are persistent and lead to impaired intellectual functions and adaptive skills in the academic, social and practical spheres. They are combined with concomitant somatic and mental disorders, which requires a well-thought-out, individual and comprehensive diagnosis at different stages of life. Progressive approaches to the diagnosis of intellectual development disorders involve strengthening and expanding diagnostic criteria: increasing the IQ values that indicate its violation; focusing not on specific IQ values, but on indicators of its deviation from the average values for the corresponding population; determining not only IQ, but also adaptive skills of children in academic, social and practical spheres.